2017
DOI: 10.1107/s2052520617007016
|View full text |Cite
|
Sign up to set email alerts
|

Experimental charge-density studies: data reduction and model quality: the more the better?

Abstract: In this review, recent developments concerning data and model quality in experimental charge-density investigations from a personal view-point are described. Data quality is not only achieved by the high resolution, high I/σ(I) values, low merging R values and high multiplicity. The quality of the innermost reflections especially is crucial for mapping the density distribution of the outermost valence electrons and can be monitored by (I/σ). New detector technologies seem to be promising improvements. Empirica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 93 publications
0
5
0
1
Order By: Relevance
“…The κ and κ′ parameters of hydrogen atoms were fixed to a value of 1.2. Crystallographic output and a detailed evaluation of the fit are given in Figures S1–S4 in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The κ and κ′ parameters of hydrogen atoms were fixed to a value of 1.2. Crystallographic output and a detailed evaluation of the fit are given in Figures S1–S4 in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Considering that the oxidation state of Cu and the associated valence electron count of the CF 3 ligands are strongly related to the electron density distribution (EDD), it is surprising that the latter has not seized a more prominent role in the many experimental and theoretical contributions. The fact is that the EDD is obtainable from accurate single-crystal X-ray diffraction experiments using a multipole model and has been used in numerous studies to provide insight into the question of molecular reactivity, bonding analysis, aromaticity, etc. The core of the approach is the fitting of population parameters related to atom-centered spherical harmonic functions, as proposed by Hansen and Coppens, and this advanced modeling requires data of the utmost quality. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Multipole refinements for all data sets were carried out using the MOPRO suite , combined with the current version of the University at Buffalo Data Bank (UBDB), which employs the Hansen–Coppens multipole model . Full details are present in the Supporting Information. , Despite the relatively low extreme values in the residual density and quite satisfactory R -factors, inspection of the residual density distribution revealed some systematic effects in the solvent molecule fragment, namely around the O4 oxygen atom (Figure a). Careful examination indicated that mostly the high-angle data are responsible for the presence of these spurious features suggesting that the observed model deficiencies are related to some inappropriate thermal motion description of this atom.…”
Section: Methodsmentioning
confidence: 99%
“…Total PDF and its anharmonic part for sulfur atoms S(1a) and S(1b) are shown in Figure S6. Refinement of thermal motion anharmonicity was justified by meeting certain conditions described in the literature; 58 namely, the R values dropped quite considerably, and, for both sulfur atoms, some of the coefficients were at least three times larger than their esd. One of the most important validation criteria, namely, the coherence of topological analysis of the experimental ED modeled, is further discussed in detail.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%